1975
DOI: 10.1037/0096-3445.104.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Probing for hypotheses with adults and children: Blank trials and introtacts.

Abstract: This paper discusses two probe techniques (blank trials and introtacts) in explorations of problem solving by adults and children. Originally, the blank-trial probe was developed by Levine (1966) to detect the nature of adults' processing in discrimination-learning tasks; it consists of a series of no-feedback ("blank") trials which are inserted between each feedback trial. This probe yielded extremely orderly data and directly validated an emerging theory of human discrimination learning, hypothesis (H) theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
4

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 17 publications
2
43
4
Order By: Relevance
“…Within each problem the pattern of presentation of the clothing items was standardised to follow the kind of "orthogonal" sequence originally devised by Levine (1966) Early studies of hypothesis-testing deduced subjects' hypotheses on an MDL task simply from their pattern of choices, using Levine's (1966) blank-trial procedure. More recently, Phillips and Levine (1975) and Kemler (1978) demonstrated that this procedure led to an underestimation of children's problem-solving abilities, and that supplementing this by asking children for verbal "hypotheses" (sometimes referred to as "introtacts") provided a more accurate picture. This procedure was, therefore, adopted within the present study, with the children being asked on each trial which card they thought represented Anna (or for "negative information" type problems which twin the one card shown represented).…”
Section: Methodology and Research Designmentioning
confidence: 99%
“…Within each problem the pattern of presentation of the clothing items was standardised to follow the kind of "orthogonal" sequence originally devised by Levine (1966) Early studies of hypothesis-testing deduced subjects' hypotheses on an MDL task simply from their pattern of choices, using Levine's (1966) blank-trial procedure. More recently, Phillips and Levine (1975) and Kemler (1978) demonstrated that this procedure led to an underestimation of children's problem-solving abilities, and that supplementing this by asking children for verbal "hypotheses" (sometimes referred to as "introtacts") provided a more accurate picture. This procedure was, therefore, adopted within the present study, with the children being asked on each trial which card they thought represented Anna (or for "negative information" type problems which twin the one card shown represented).…”
Section: Methodology and Research Designmentioning
confidence: 99%
“…However, the first explanation seems to fit the results of the slow learning children, whereas the second and third explanations seem more likely in the nonlearning children, as judged by the estimated accuracies. Latent learning modeling of performance on learning tasks that involve blank trials may help to distinguish between these strategies (Phillips & Levine, 1975). However, performance is expected to suffer in these tasks because blank trial tasks are more demanding.…”
Section: Switchingmentioning
confidence: 99%
“…Studies of the hypothesis testing behavior of children suggest that young children might not apply the strict win-stay and lose-shift substrategies (Gholson, Levine, & Phillips, 1972;Kemler, 1978;Phillips & Levine, 1975). However, these studies arrived at different conclusions, specifically concerning the use of the lose-shift substrategy in the age range of 4 to 10.5 years.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, first graders cannot demonstrate the strategies in the context in which they were taught, let alone transfer such strategies (see also, e.g., Canton & Spiker, 1978;Phillips & Levine, 1975).…”
Section: Theoretical And/or Literature Basementioning
confidence: 99%